2021
DOI: 10.1002/fsn3.2373
|View full text |Cite
|
Sign up to set email alerts
|

Dietary association of iron deficiency anemia and related pregnancy outcomes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It is commonly known that anemia in pregnancy increases the risk of pre-term birth and low birth weight [ 15 , 17 , 68 , 94 , 95 ]. It is estimated that, if anemia develops in women with a twin pregnancy at 12 weeks, the risk of pre-term birth increases to 29–68%, while if it happens at 16–18 weeks, the risk is three- to four-fold [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly known that anemia in pregnancy increases the risk of pre-term birth and low birth weight [ 15 , 17 , 68 , 94 , 95 ]. It is estimated that, if anemia develops in women with a twin pregnancy at 12 weeks, the risk of pre-term birth increases to 29–68%, while if it happens at 16–18 weeks, the risk is three- to four-fold [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Africa, a large percentage of pregnant mothers remain malnourished, and maternal nutrition and infant health are closely correlated. Maternal anemia and low birth weight remain major public health problems in developing countries (Zulfiqar et al, 2021). This study aimed to examine a pooled estimate of the association between dietary diversity during pregnancy, maternal anemia, and low birth weight in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal anemia and low birth weight remain major public health problems in developing countries (Zulfiqar et al, 2021). This study aimed to examine a pooled estimate of the association between dietary diversity during pregnancy, maternal anemia, and low birth weight in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a few studies have found that inadequate iron intake is associated with insufficient red blood cells and leads to iron deficiency anemia [ 27 ]. About 25% of all maternal deaths globally are associated with severe anemia iron deficiency and a significant risk for maternal bleeding, premature birth, and having a baby with low birth weight [ 28 ].…”
Section: Discussionmentioning
confidence: 99%